Edukasi Praktek Ubudiyah Dan BTQ (Baca Tulis Qur’an) Di Ponpes Al-Mukhtar Semen Kediri - Nabilatun Nada; Miksan Ansori (LP3M IAIFA Kediri, 2022)
The spirit of learning students is also a reason that must be developed, because with this reason Ponpes al-Mukhtar will further develop through the outputs of its students. Through a long period of research Ponpes al-Mukhtar is still lacking in the application of jurisprudence. Therefore, researchers will accompany in the addition of more in-depth religious knowledge material. The purpose of this mentoring activity is none other than to prepare cadres who are able to worship in accordance with the rules that have been shari'a, because women are the first educators as well as the first school for children. The process was supported by BTQ activities. The purpose of BTQ itself is to preserve and prepare the next generation to become a generation that loves the Qur'an and even makes the Qur'an a view of life. Thus, the next generation is able to worship and uphold islam according to Shari'a.